Food sustainability perception at universities: Education and demographic features effects. Issue 2 (July 2022) - Massaglia, S.; Peano, C.; Merlino, V.M.; Gregis, A.; Ghisalberti, C.; Sottile, F.
Abstract: The 2030 Agenda of the United Nations merged in 17 goals the strong need to change the pattern of human life on the planet in a path of strengthening sustainability especially in an era that is widely defined as Anthropocene. The Global Action Program (GAP) on Education and Sustainable Development was adopted based on the power of education and knowledge with the idea of 'green universities' aimed at improving the perception of sustainability for future policy decisions. Based on a Best-Worst (BW) scaling methodological approach, in this study we quantified the preferences of generation Y at University of Turin as they relate to issues explicitly connected to the ordinary consumption of food and the relationship between this and the perception of a sustainable approach. Data show that sustainability definitions belonging to the environmental and policy dimensions were the most closely related to the sustainability concept by the students interviewed while the economic and socio-cultural spheres were the least appreciated. In relation to food issues, students generally don't attribute high value to the assessment of local production. Few but significant differences were found in some specific topics between male and female groups with women perceiving sustainability consistently linked to the concept of local/territory and to the protection of the environment. Highlights: The environmental and policy issues impact on student's sustainability perception. Students generally don't attribute high value to the assessment of local production. The gender affects the sustainability perception by the Y generation students. Women linked the sustainability issue to the territory/environmental protection need. The university programme influences the perception of the sustainability dimensions.